2023
DOI: 10.26493/1855-3974.2683.5f3
|View full text |Cite
|
Sign up to set email alerts
|

Almost simple groups as flag-transitive automorphism groups of symmetric designs with λ prime

Abstract: In this article, we study symmetric designs with λ prime admitting a flag-transitive and point-primitive automorphism group G of almost simple type with socle X. We prove that either D is one of the six well-known examples of biplanes and triplanes, or D is the pointhyperplane design of PG(n−1, q) with λ = (q n−2 −1)/(q −1) prime and X = PSL n (q).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…In 2020, reduction concerning symmetric designs with λ $\lambda $ prime was studied in [16]. Recently, under the same condition, the classification of automorphism groups with simple socle was finished in [1]. Hence the present paper extends the results from symmetric designs to nonsymmetric 2‐designs.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…In 2020, reduction concerning symmetric designs with λ $\lambda $ prime was studied in [16]. Recently, under the same condition, the classification of automorphism groups with simple socle was finished in [1]. Hence the present paper extends the results from symmetric designs to nonsymmetric 2‐designs.…”
Section: Introductionmentioning
confidence: 75%
“…Since ≤ ≀ G H S 2 , the flag-transitivity of G implies that ω r 2 divides   H 2 2 , which is impossible for all cases except that z ω λ ( , , ) is (1, 9, 7), (1, 21, 5), (1,33,31) and (4, 21, 5). The four exceptions are ruled out by using the computer software MAGMA [2] with exactly the same procedure in [15,Lemma 3.6], which contains the following four steps:…”
Section: The Case M =mentioning
confidence: 99%
See 2 more Smart Citations
“…In [1], applying the O'Nan-Scott theorem, the first author and Zhou showed that flag-transitive, point-primitive automorphism groups of such symmetric designs have either an abelian socle or a nonabelian simple socle. Alavi et al, in [2], further completed the classification of these designs when the automorphism group has a non-abelian simple socle. In 1993, Praeger established an analog of the O'Nan-Scott theorem for quasiprimitive groups in [3], which implies the possibility of determining the socle of the point-quasiprimitive automorphism group of 2-designs.…”
Section: Introductionmentioning
confidence: 99%